Differential repression of specific mRNA in erythroblast cytoplasm: a possible role for free mRNP proteins. - Vincent, A (1983)
Two types of in vivo untranslated 'free' mRNA-protein particles (mRNP) were isolated from duck erythroblast cytoplasm and characterised. Both types, namely the highly purified globin mRNA-specific '20S' mRNP and the '35S' mRNP containing a heterogenous non-globin mRNA population, are not translatable in rabbit reticulocyte lysates, but yield active mRNA upon deproteinisation. In vivo, 90% of globin mRNA is translated, but the majority of mRNA types are found in the inactive mRNP fraction, including fully repressed mRNA species. Searching for the factors controlling differential mRNA repression, we characterised and compared the protein composition of globin and '35S' mRNP using two dimensional gel electrophoresis, in vivo labelling with [35S]methionine and in vivo phosphorylation. The major proteins ubiquitously bound to globin or any other mRNA in the polyribosomes (e.g., the 73 K mol. wt. poly(A) binding protein) were not detected in purified inactive mRNP. In the latter some polypeptides appear to be associated with only one of the two inactive mRNA types while some others are common to both mRNPs. Furthermore, different rates of synthesis and phosphorylation characterize the protein populations of the two types of repressed mRNP. The specificity in composition and metabolism of the populations of polypeptides associated with different subpopulations of inactive cytoplasmic mRNA, as shown here, argues in favour of a role of mRNP proteins in mRNA recognition and selective translational repression, possibly in association with the ScRNA previously found as components of the free mRNP and able to inhibit protein synthesis.